2017
DOI: 10.1093/hropen/hox014
|View full text |Cite
|
Sign up to set email alerts
|

rs10732516 polymorphism at the IGF2/H19 locus associates with a genotype-specific trend in placental DNA methylation and head circumference of prenatally alcohol-exposed newborns

Abstract: Study Question Does prenatal alcohol exposure (PAE) affect regulation of the insulin-like growth factor 2 (IGF2)/H19 locus in placenta and the growth-restricted phenotype of newborns? Summary Answer PAE results in genotype-specific trends in both placental DNA methylation at the IGF2/H19 locus and head circumference (HC) of newborns. What is Known Already PAE can disturb development of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 54 publications
(66 reference statements)
4
25
2
Order By: Relevance
“…Of note, our finding that alcohol exposure was associated with increased IGF2 expression in this sample is consistent with previous reports of alcohol-related increases in expression in human placenta trophoblast cultures (Joya et al, 2015), rat placental tissue (G ardebjer et al, 2014), hippocampus (Tunc-Ozcan et al, 2016), and human whole blood through age 5 years (Aros et al, 2011). Two studies have shown decreased placental IGF2 expression (1 human [Marjonen et al, 2017], 1 mouse [Downing et al, 2011]). For 5 imprinted genes (ZIM2, PEG10, IFG2AS, NNAT, and IGF2), alcohol-related alterations in placental expression statistically mediated the effects of prenatal alcohol exposure on length, suggesting that alcohol-related expression changes in these genes (i) serve as a marker for physiologic processes that lead to postnatal growth restriction, (ii) set off a cascade of downstream events that contribute to postnatal growth restriction, and/or (iii) represent expression changes that persist postnatally and contribute to postnatal growth restriction.…”
Section: Igf2supporting
confidence: 92%
See 1 more Smart Citation
“…Of note, our finding that alcohol exposure was associated with increased IGF2 expression in this sample is consistent with previous reports of alcohol-related increases in expression in human placenta trophoblast cultures (Joya et al, 2015), rat placental tissue (G ardebjer et al, 2014), hippocampus (Tunc-Ozcan et al, 2016), and human whole blood through age 5 years (Aros et al, 2011). Two studies have shown decreased placental IGF2 expression (1 human [Marjonen et al, 2017], 1 mouse [Downing et al, 2011]). For 5 imprinted genes (ZIM2, PEG10, IFG2AS, NNAT, and IGF2), alcohol-related alterations in placental expression statistically mediated the effects of prenatal alcohol exposure on length, suggesting that alcohol-related expression changes in these genes (i) serve as a marker for physiologic processes that lead to postnatal growth restriction, (ii) set off a cascade of downstream events that contribute to postnatal growth restriction, and/or (iii) represent expression changes that persist postnatally and contribute to postnatal growth restriction.…”
Section: Igf2supporting
confidence: 92%
“…(1 human [Marjonen et al, 2017] and 1 mouse [Downing et al, 2011]) LGA, large-for-gestational age; FASD, fetal alcohol spectrum disorders; IUGR, intrauterine growth restricting; DMR, differentially methylated region; ICR, imprinting control region.…”
Section: Igf2mentioning
confidence: 99%
“…In previous studies, it has been shown that hypermethylation at H19 ICR in Beckwith-Wiedemann syndrome with fetal over-growth leads to overexpression of IGF2 and downregulation of H19 , and conversely, hypomethylation of H19 ICR in Silver-Russell syndrome with growth restriction leads to downregulation of IGF2 and biallelic expression of H19 [ 34 , 35 ]. In addition, in our previous human study, we observed significantly increased expression of H19 in relation to IGF2 when comparing all alcohol-exposed placentas to unexposed controls [ 5 ]. Therefore, we decided to explore if prenatal alcohol exposure has affected the DNA methylation level of the locus and consequently the regulation of Igf2 and H19 .…”
Section: Resultsmentioning
confidence: 91%
“…The molecular mechanisms of PAE have been under extensive research, and the epigenetic variation induced in utero is a strong candidate mediator [ 3 5 ]. Previously, we have developed a mouse model of early PAE, based on maternal ad libitum ingestion of 10% (v/v) alcohol and took advantage of a mouse strain C57BL/6, which has a strong drinking preference for 10% alcohol [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation